How Do Parents Use Online Communities? An Analysis of the r/Parenting Subreddit - Lieb, Anna; Chapekis, Athena; Shah, Sono; Smith, Aaron (Proceedings of the International AAAI Conference on Web and Social Media, 2026)
As today’s parents navigate the challenges of raising a child, many are turning to online spaces where fellow parents share their experiences. To better understand parents' use of online communities, we conduct a two-part analysis of data from (1) the r/Parenting subreddit and (2) a nationally representative survey of U.S. parents. Based on 29,295 posts and 853,209 comments collected from r/Parenting, we find that about half of posts express negative emotions — yet the vast majority of comments in reply to these posts are supportive. We also surface themes from three salient topics that appear in posts on the subreddit. Survey data from a sample of 3,054 parents of children ages 12 and under complements the Reddit analysis by providing insight on how parents use online communities in day-to-day life. We find that about two-thirds of U.S. parents say they visit online parenting communities, and that mothers, young parents, parents with young children, and parents with lower incomes are especially likely to do so. Overall, we leverage both data sources to characterize who participates in online parenting communities, what they discuss there, and how parents experience these online spaces.